SYSTEM OF INTERNATIONAL COOPERATION FOR SUSTAINABLE DEVELOPMENT IN THE AREA OF COMBATING HUMAN TRAFFICKING IN THE 21ST CENTURY - Kownacki, Tomasz (Torun International Studies, 2021)
The problem of international cooperation for sustainable development in the areas of environmental protection, economics, energy and public goods is a well-known scope of research, which can be classified as a classic canon of analysis in this domain. There is an explicit lack of research in the area of security, particularly in those aspects relating to objectives 8 and 16 of Agenda 2030, referring to combating the crime of human trade. The aim of the publication is to analyse the dynamics of international cooperation for the implementation of sustainable principles in the fight against human trafficking, undertaken in the context of the diagnosis of its effects for the implementation of sustainable principles with the use of resources (created and implemented standards), cooperation structures (global international organisations and their Member States) forming a system of international cooperation, the directions of which are determined by security needs. The article shows the evolution of international law in this area, the cooperation of selected international structures and its effects, as well as the dynamics of change resulting from statistics indicating the directions of implementation of objectives 8 and 16 of the sustainable development of the Agenda 2030. To achieve the objective, the assumptions of institutional theory were applied. The analysis was made using historical, comparative methods and analysis of source documents. The analysis presented in the article allows us to conclude that after the adoption of the Agenda 2030, the dynamics of international cooperation in the analysed area has increased, which is reflected in the new impetus given to the implementation of provisions enshrined in international law and required actions undertaken by member states - signatories of the act. Combating the crime of trafficking in human beings takes place within the framework of a diagnosable multifaceted institutional formula expressed in a detailed division of tasks and competences, allowing for coordination at the global level of preventive and operational actions to combat this practice. Global international cooperation for sustainable development in the area of combating trafficking in human beings in the 21st century is implemented in a systemic way and brings results which provide better and better prospects for effective combating of this crime, thus meeting the assumptions and objectives 8 (p. 8.7) and 16 (p. 16.2) of the Agenda 2030.